Field Guide to Oregon Rivers - Palmer, Tim, 1948- (Book collections on Project MUSE., 2014)
Despite Oregon's watery reputation, the state has lacked a field guide for its many celebrated rivers and streams--until now. Preeminent river conservationist, photographer, and author Tim Palmer's Field Guide to Oregon Rivers is an unprecedented reference that profiles 120 waterways throughout the state, from the Alsea to the Williamson. Field Guide to Oregon Rivers offers travelers, outdoor enthusiasts, and resource professionals an interpretive approach to the state's network of waterways. The book begins with a natural history of Oregon's rivers--geology, climate, hydrology, plants, animals, and ecology. Then in ten chapters organized by watersheds, Palmer presents portraits of individual rivers, with a summary of its character, notes about its nature and fish, and comments about ongoing threats along with protection efforts. He points to opportunities for seeing the river, hiking along its shores, fishing, and exploring by canoe, kayak, raft, or drift boat. The guide concludes with a series of appendices addressing the Best River Running, the Best Hiking Along Rivers, the Best Fishing, Oregon's Finest Natural Rivers, and more.